Antioxodative, anti-inflammatory and antimycobacterial activities of artemisia afra subfraction against mycobacterium smegmatis - Matlala, Mabasa Precious (My University, 2025)
Tuberculosis (TB) is a well-known communicable disease discovered decades back and continues to be a persistent socio-economic burden worldwide with the increasing number of multidrug-resistant and extensive-drug resistant forms. Medicinal plants have been accredited as potential sources of natural pharmaceuticals against TB. The aim of the study was to investigate the efficacy of antioxidative, anti-inflammatory and antimycobacterial activities of Artemisia afra extracts and sub-fractions. Mycobacterium smegmatis was used as a surrogate for Mycobacterium tuberculosis (Mtb). The aerial parts of A. afra plant were dried and ground into fine powder. The powdered plant material was extracted using hexane, chloroform, dichloromethane, ethyl acetate, acetone, ethanol, butanol, methanol, and water. All the solvents demonstrated good extraction capacity. The qualitative phytochemical analysis was done using standard chemical tests and thin layer chromatography. Standard chemical tests showed the presence of saponins, steroids, tannins, cardiac glycosides, terpenes, and flavonoids in the extracts. Phytochemical analysis revealed more fluorescing compounds at 365 nm. The methanol extract had the highest amount of total phenolic (190.31±5.81 mg GAE/g), tannin (339.92±11.28 mg GAE/g) and flavonoid contents (1333.07±12.97 mg QE/g). All the tested A. afra extracts had low ferric ion reducing antioxidant power. However, the acetone extract showed notable 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical-scavenging potential. Anti-inflammatory activity was investigated using the egg-albumin denaturation assay, where the acetone extract demonstrated the higher activity than diclofenac sodium. Furthermore, the acetone extract exhibited noteworthy antimycobacterial activity against M. smegmatis observed on the three chromatograms developed in BEA, CEF and EMW mobile systems with minimum inhibitory concentration of 0.521 mg/mL. Cytotoxicity was tested against the THP-1 cell-line monocytes. The differentiation of THP-1 monocytes into macrophage-like cells was induced by phorbol 12-myristate 13-acetate (PMA). The acetone and methanol extracts had less toxicity at the lowest concentration of 125 µg/mL. Column chromatography was used to fractionate the active acetone extract; and its subfraction of intermediate polarity had the highest inhibitory activity against M. smegmatis at MIC value of 0.078mg/mL. Moreover, the subfraction was able to prevent initial cell attachment to form biofilms in a concentration dependent manner and the matured formed biofilm after 24hrs was also reduced. Growth inhibitory activity monitored in different time intervals and anti-inflammatory activity were also observed. Results obtained from LC-MS analysis revealed several compounds at different retention times from both the acetone crude extract and the sub-fraction. The crude extract contained lesser number of compounds as compared to the sub-fraction. These results suggest that the acetone sub-fraction from the aerial parts of A. afra may be a good candidate for further anti-TB drug development
Thesis (M.Sc. (Microbiology)) -- University of Limpopo, 2025
Keywords: Antioxidative; Anti-inflammatory; Antimycobacterial activities; Artemisia afra subfraction; Mycobacterium smegmatis; Mycobacterium; Artemisia; Medicinal plants; Anti-inflammatory agents